Unilateral Retinitis Pigmentosa in One Eye and Tilted Hypoplastic Disc in the Other Eye (Two in One Disease) - Ashraf EI Batarny, Upender K Wali, Muhammad Naqaish Sadiq, Jagdish Bhatia (Pakistan Journal of Ophthalmology, 2018)
We report a case of 32 year old woman who presented with night blindness in her right eye and defective vision in her both eyes. On basis of history, clinical examination, VEP and visual fields, she was diagnosed as a case of advanced unilateral retinitis pigmentosa in her right eye and hypoplasia of optic nerve in left eye with tilted disc and situs inverses. We describe this unique combination of retinal dystrophy in one eye and congenital anomaly of optic disc in other eye as two in one disease. To our knowledge this rare combination of two retinal pathology has never been reported before.